Preparation method of battery negative plate, negative plate and secondary battery

By using fiber fabrics as porous polymer substrates, a porous structure is formed and a metal layer is plated, the problems of volume expansion and poor conductivity of high-capacity negative electrode materials are solved, the stability and performance of the battery are improved, and the production cost is reduced.

CN119297294APending Publication Date: 2025-01-10JIANGXI GANFENG BATTERY TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411324754.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Conventional copper foil current collectors are difficult to accommodate volume changes in high-capacity negative electrode materials, resulting in damage to the electrode structure and poor conductivity, which affects the cycle stability and service life of the battery.

Method used

Fibrous fabrics are used as porous polymer substrates to form porous structures by physical or chemical methods, and are used to prepare battery negative electrode sheets, providing space for high-capacity negative electrode material volume changes, and improving conductivity through metal layer plating.

Benefits of technology

It improves the stability and conductivity of the electrode, reduces the production cost of the battery, extends the service life of the battery, and improves the energy density and rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297294A_ABST
    Figure CN119297294A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a battery negative electrode plate, a negative electrode plate and a secondary battery, and the preparation method comprises the following steps: reserving an empty foil tab position on a negative electrode current collector, and dipping and coating in negative electrode slurry for a certain time to obtain a dipped negative electrode plate; drying the soaked negative electrode plate to obtain a dried negative electrode plate; the negative current collector comprises a current collector substrate and a functional layer, the functional layer is arranged on the surface of the current collector substrate, and the current collector substrate has a porous structure; according to the invention, the fiber fabric is used as a porous polymer substrate, the fiber fabric is randomly arranged by a physical or chemical method, a large number of pore structures are formed in the fiber fabric, and the pore structures not only have excellent permeability, but also can provide enough space for the high-capacity negative electrode material to generate volume change in the charging and discharging process; the stability of the electrode is improved; and the good permeability of the fiber fabric is beneficial to uniform distribution of electrolyte and rapid transmission of lithium ions, so that the energy density and the rate capability of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of lithium ion batteries, and in particular to a method for preparing a negative electrode sheet of a battery, a negative electrode sheet and a secondary battery. Background Art

[0002] The structure of conventional copper foil current collector is relatively dense, which makes it difficult to effectively accommodate the volume change of high-capacity negative electrode materials, resulting in the destruction of the electrode structure. In addition, the bonding force between high-capacity negative electrode materials and conventional copper foil current collector is relatively weak, which is easy to fall off during the charge and discharge cycle, which not only reduces the capacity retention rate of the battery, but also increases the internal resistance of the battery, thereby affecting the cycle stability and service life of the battery.

[0003] In this context, researchers are constantly exploring new methods to improve the performance of high-capacity negative electrode materials. Among them, the application of porous current collectors is considered to be an effective solution. Porous current collectors can not only provide sufficient space for the volume expansion of high-capacity negative electrode materials, but also promote the penetration of electrolytes and the transmission of lithium ions, thereby improving the overall performance of the battery. However, common three-dimensional porous current collectors such as copper foam and nickel foam have a large number of pore structures, which leads to a decrease in their mechanical strength. Especially under high current density and long cycle conditions, structural collapse or deformation is prone to occur; and the foam materials prepared by conventional template methods are relatively thick (greater than 500μm), which cannot meet the actual needs of current high-energy lithium-ion batteries.

[0004] High-capacity anode materials, such as pure silicon, silicon-carbon, silicon-oxygen, and hard carbon, have the advantage of high specific capacity (the theoretical specific capacity of pure silicon is about 10 times that of traditional graphite anodes). This makes high-capacity anode materials have great potential in improving battery energy density, but they also face many challenges in practical applications: Volume expansion: High-capacity negative electrodes will undergo significant volume expansion during the lithiation process (for example, the volume expansion of pure silicon can reach 300%), which will lead to the destruction of the electrode structure and rapid capacity decay.

[0005] Poor conductivity: Silicon-based materials have relatively poor conductivity, which affects the overall performance of the battery.

[0006] To this end, we propose a method for preparing a battery negative electrode sheet, a negative electrode sheet and a secondary battery to solve the problems of volume expansion and poor conductivity. Summary of the invention

[0007] The purpose of the present invention is to solve the shortcomings existing in the prior art. In order to achieve the above purpose, the present invention adopts the following technical solutions: A method for preparing a negative electrode sheet of a battery comprises the following steps: S1: leaving an empty foil tab position for the negative electrode current collector, immersing and coating it in the negative electrode slurry for a certain period of time to obtain an immersed negative electrode sheet; S2: drying the impregnated negative electrode sheet to obtain a dry negative electrode sheet; The negative electrode current collector comprises a current collector matrix and a functional layer, wherein the functional layer is arranged on the surface of the current collector matrix, and the current collector matrix has a porous structure.

[0008] Further preferably, the current collector matrix is ​​a porous polymer, the functional layer is a metal layer, and the metal layer is plated on the surface of the porous polymer by vacuum plating, electroplating, or chemical plating; and the porous polymer is a fiber fabric.

[0009] Further preferably, the negative electrode slurry consists of a main material, a conductive agent, a binder, and a solvent, and the main material includes one or more of graphite, silicon carbon, silicon oxygen, and hard carbon.

[0010] Further preferably, the conductive agent includes one or more of carbon nanotubes, carbon black, and acetylene black.

[0011] Further preferably, the binder includes one or more of styrene-butadiene rubber (SBR), sodium carboxymethyl cellulose (CMC), and polyacrylic acid (PAA).

[0012] Further preferably, the solvent includes one or more of deionized water, NMP, and DMF.

[0013] More preferably, the immersion coating time of the current collector substrate is 10 to 30 seconds.

[0014] More preferably, the drying temperature of the impregnated negative electrode sheet is 60-140° C., and the drying time is 5-180 s.

[0015] A negative electrode sheet, a battery negative electrode sheet made according to any one of the preparation methods described above.

[0016] A secondary battery is a battery made according to the battery negative electrode sheet described above.

[0017] Compared with the prior art, the present invention has the following beneficial effects: The present invention uses a fiber fabric as a porous polymer substrate. The fiber fabric is randomly arranged by physical or chemical methods, and a large number of pore structures are formed inside the fiber fabric. These pore structures not only have excellent permeability, but also can provide sufficient space for the high-capacity negative electrode material to undergo volume changes during the charge and discharge process, thereby improving the stability of the electrode. Secondly, the good permeability of the fiber fabric helps the uniform distribution of the electrolyte and the rapid transmission of lithium ions, thereby improving the energy density and rate performance of the battery; In addition, fiber fabrics are low-cost and have simple production processes, which are conducive to reducing battery production costs and improving market competitiveness. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a schematic diagram of the structure of the PET copper-plated three-dimensional porous current collector; Figure 2 The SEM image and Cu element distribution image of PET copper-plated three-dimensional porous current collector; Figure 3 It is a schematic diagram of the dip coating process and equipment structure; Figure 4 Schematic diagram of the structure of the composite electrode prepared for the three-dimensional porous current collector.

[0019] In the figure: driven roller 1, automatic glue sticking machine 2, coating box 3, dipping roller 4, scraper 5, pressure roller 6, drying box 7, automatic glue peeling machine 8, active roller 9. DETAILED DESCRIPTION

[0020] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0021] Reference Figure 1-Figure 4 A method for preparing a negative electrode sheet of a battery comprises the following steps: S1: leaving an empty foil tab position for the negative electrode current collector, immersing and coating it in the negative electrode slurry for a certain period of time to obtain an immersed negative electrode sheet; S2: drying the impregnated negative electrode sheet to obtain a dry negative electrode sheet; The negative electrode current collector comprises a current collector matrix and a functional layer, wherein the functional layer is arranged on the surface of the current collector matrix, and the current collector matrix has a porous structure.

[0022] The current collector matrix is ​​a porous polymer, the functional layer is a metal layer, and the metal layer is plated on the surface of the porous polymer by vacuum plating, electroplating, or chemical plating; the porous polymer is a fiber fabric.

[0023] In the embodiment, the fiber fabric is a flexible non-conductive polymer fiber fabric, including PET, PP, PE, PI, PVA, PVC, etc., and the plated metal includes copper, nickel, etc.; the metal plated layer has a uniform thickness of 0.1-3 μm, the overall thickness of the porous current collector is 20-200 μm, the pore size range is 1-200 μm, the porosity is 50-99%, and the surface density is 5-300 g / m 2 .

[0024] In one embodiment, the fiber fabric is PET, and a composite material is prepared by uniformly plating copper on its surface, and the composite negative electrode is prepared by using the composite material as a porous current collector; Figure 1 The actual picture of the three-dimensional porous current collector prepared by PET copper plating shows that the composite material prepared by PET copper plating has a smooth surface, obvious metallic luster, relatively uniform color, and obvious porous properties, showing good flexibility and certain tensile strength; Figure 2 The SEM image of the three-dimensional porous current collector prepared by copper plating on PET shows that fibers with a diameter of 10-20 μm are interwoven to form a PET substrate, thereby constructing a three-dimensional porous structure, and the mapping of the copper element shows that it is evenly distributed on the fiber surface; Figure 4 Schematic diagram of a composite electrode prepared with a three-dimensional porous current collector, with copper-plated PET in the middle and SiC on both sides. It can be seen that the negative electrode silicon-carbon slurry is partially infiltrated in the three-dimensional network structure of the copper-plated PET. The degree of infiltration depends on the current collector thickness, porosity and infiltration time.

[0025] In one embodiment: the fiber fabric is a non-woven fabric, which is formed by randomly arranging fibers through physical or chemical methods, and a large number of pore structures are formed inside the non-woven fabric. These pore structures not only have excellent permeability, but also can provide sufficient space for high-capacity negative electrode materials to undergo volume changes during charging and discharging, thereby improving the stability of the electrode; the good permeability of the non-woven fabric contributes to the uniform distribution of the electrolyte and the rapid transmission of lithium ions, thereby improving the energy density and rate performance of the battery; the non-woven fabric material has low cost and simple production process, which is conducive to reducing the production cost of the battery and improving the market competitiveness.

[0026] The negative electrode slurry is composed of a main material, a conductive agent, a binder, and a solvent. The main material includes one or more of graphite, silicon carbon, silicon oxygen, and hard carbon; the conductive agent includes one or more of carbon nanotubes, carbon black, and acetylene black; the binder includes one or more of styrene-butadiene rubber (SBR), sodium carboxymethyl cellulose (CMC), and polyacrylic acid (PAA); the solvent includes one or more of deionized water, NMP, and DMF; the immersion coating time of the current collector matrix is ​​10 to 30 seconds; the drying temperature of the immersed negative electrode sheet is 60 to 140°C, and the time is 5 to 180 seconds.

[0027] A negative electrode sheet, a battery negative electrode sheet made according to any one of the preparation methods described above.

[0028] In the embodiment: Preparation of negative electrode sheet: A porous current collector roll with a width of 100 mm, a thickness of 60 μm and a porosity of 80% is selected and placed on a driven roller 1. The 14 mm width area of ​​the edge of the electrode is glued by an automatic glue sticking machine 2 to prevent the slurry from being impregnated. Then, the dip coating roller 4 is immersed in a coating box 3 filled with negative electrode silicon-carbon slurry to a certain depth for dip coating for 10 s. Then, the excess slurry on the surface is scraped off with a scraper 5, and the roll is rolled to 40 μm by a pressing roller 6. After being baked at 100°C for 120 s in a drying oven 7, the tape is removed by an automatic glue tearing machine 8, and finally rolled up by an active roller 9.

[0029] A secondary battery is a battery made according to the battery negative electrode sheet described above, and the battery comprises a soft pack, a square aluminum shell and a cylindrical battery.

[0030] In the embodiment: Preparation of soft pack battery: A mixture of 200 g of positive electrode active material lithium nickel cobalt manganese oxide (NCM), 5.3 g of binder polyvinylidene fluoride (PVDF), and 5.3 g of conductive agent acetylene black was added to 140 g of N-methyl-2-pyrrolidone (NMP), and then stirred in a vacuum mixer to form a uniform positive electrode slurry. The slurry was evenly coated on a 16-micron thick aluminum foil, and the coating surface density was controlled to be 39.8 g / cm 2 , and then dried at 120°C to obtain the positive electrode sheet.

[0031] The composite negative electrode sheet, positive electrode sheet and separator prepared above are alternately stacked in a "Z" shape, the positive electrode tab is ultrasonically welded to the aluminum sheet, and the negative electrode tab is ultrasonically welded to the nickel-plated copper, and then pre-sealed with an aluminum-plastic film, and then an electrolyte (ethylene carbonate: methyl ethyl carbonate: diethyl carbonate in a volume ratio of 1:1:1, containing 1 mol of lithium hexafluorophosphate) is injected into the above battery, and it is formed in a conventional manner to obtain a lithium-ion battery.

[0032] Comparative Example: The batteries in the control group were prepared using the same steps as above, except that only the porous current collector was replaced with a traditional 8μm copper foil. All batteries were tested for electrochemical performance and cell expansion.

[0033] Experimental test data: The initial thickness of the experimental battery cell in the control embodiment is 5.5 mm. After 100 cycles, the capacity retention rate is 99.7%, the thickness increases to 6.8 mm, and the expansion rate is 23.6%. The test data of the porous current collector of the present invention is that the initial thickness of the battery cell is 5.7 mm, the capacity retention rate is 99.8% after 100 cycles, the thickness increases to 6.1 mm, and the expansion rate is 7.0%.

[0034] The theoretical volume expansion of the composite negative electrode prepared by the present invention is <10%, while the volume expansion of the negative electrode prepared by using the traditional copper foil current collector is 30%~40%. It can be seen that the former has a significant effect of slowing down the volume expansion.

[0035] The present invention uses fiber fabric as a porous polymer substrate. The fiber fabric is randomly arranged by physical or chemical methods, and a large number of pore structures are formed inside the fiber fabric. These pore structures not only have excellent permeability, but also can provide sufficient space for high-capacity negative electrode materials to undergo volume changes during charging and discharging, thereby improving the stability of the electrode; secondly, the good permeability of the fiber fabric is conducive to the uniform distribution of the electrolyte and the rapid transmission of lithium ions, thereby improving the energy density and rate performance of the battery; in addition, the fiber fabric is low in cost and simple in production process, which is conducive to reducing the production cost of the battery and improving the market competitiveness.

Claims

1. A method for preparing a negative electrode sheet of a battery, characterized in that: The following steps are involved: S1: leaving an empty foil tab position for the negative electrode current collector, immersing and coating it in the negative electrode slurry for a certain period of time to obtain an immersed negative electrode sheet; S2: drying the impregnated negative electrode sheet to obtain a dry negative electrode sheet; The negative electrode current collector comprises a current collector matrix and a functional layer, wherein the functional layer is arranged on the surface of the current collector matrix, and the current collector matrix has a porous structure.

2. The method for preparing a negative electrode sheet of a battery according to claim 1, characterized in that: The current collector matrix is ​​a porous polymer, the functional layer is a metal layer, and the metal layer is plated on the surface of the porous polymer by vacuum plating, electroplating, or chemical plating; the porous polymer is a fiber fabric.

3. The method for preparing a negative electrode sheet of a battery according to claim 1, characterized in that: The negative electrode slurry is composed of a main material, a conductive agent, a binder, and a solvent. The main material includes one or more of graphite, silicon carbon, silicon oxygen, and hard carbon.

4. The method for preparing a negative electrode sheet of a battery according to claim 3, characterized in that: The conductive agent includes one or more of carbon nanotubes, carbon black, and acetylene black.

5. The method for preparing a negative electrode sheet of a battery according to claim 3, characterized in that: The binder includes one or more of styrene-butadiene rubber (SBR), sodium carboxymethyl cellulose (CMC), and polyacrylic acid (PAA).

6. The method for preparing a negative electrode sheet of a battery according to claim 3, characterized in that: The solvent includes one or more of deionized water, NMP, and DMF.

7. The method for preparing a negative electrode sheet of a battery according to claim 1, characterized in that: The immersion coating time of the current collector substrate is 10 to 30 seconds.

8. The method for preparing a negative electrode sheet of a battery according to claim 1, characterized in that: The drying temperature of the impregnated negative electrode sheet is 60-140° C., and the drying time is 5-180 s.

9. A negative electrode sheet, characterized in that: A battery negative electrode sheet prepared by the preparation method according to any one of claims 1 to 8.

10. A secondary battery, characterized in that: A battery made from the battery negative electrode sheet according to claim 9.